Asymmetric Transfer Hydrogenation of Ketones with Modified Grubbs Metathesis Catalysts: On the Way to a Tandem Process. Issue 4 (26th January 2016) - Renom‐Carrasco, Marc; Gajewski, Piotr; Pignataro, Luca; de Vries, Johannes G.; Piarulli, Umberto; Gennari, Cesare; Lefort, Laurent
Abstract: Herein, we report the successful transformation of a 1 st generation Grubbs metathesis catalyst into an asymmetric transfer hydrogenation (ATH) catalyst. Upon addition of a chiral amine ligand, an alcohol and a base, the 1 st generation Hoveyda–Grubbs catalyst (HG‐I ) was found to promote the enantioselective reduction of acetophenone to 1‐phenylethanol. After optimizing the order of addition and the reaction conditions, the substrate scope was assessed leading to enantiomeric excesses up to 97% ee . NMR experiments were run in order to get information about the in situ ‐generated ATH catalyst. Furthermore, the possibility to perform olefin metathesis and ketone transfer hydrogenation sequentially in one pot was demonstrated, and the first tandem olefin metathesis–ketone asymmetric transfer hydrogenation was carried out. Abstract :